Meningkatkan Motivasi dan Kecerdasan SMA Melalui Lomba Cerdas Cermat di Kota Pematangsiantar - Victor Asido Elyakim P (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
This community service activity was carried out with the aim of supporting the Coordinator of Community Policy Supervision-RI in the preparation of a technical meeting to prepare for the 2023 CabDis Cup quiz competition. This activity is designed to facilitate the preparation of competition materials that are relevant to national policies, so as to increase public understanding, especially the younger generation, of public policy issues. This community service involves a series of technical preparation activities, such as preparing meeting agendas, determining assessment criteria, and planning competition socialization strategies so that the 2023 CabDis Cup quiz competition can take place properly. The methodology used includes focused discussions with the Coordinator team, as well as the participation of Pematangsiantar City High School in the planning process so that the material and mechanism of the competition can be adjusted to the needs and interests of the participants. The results of this activity show that the role of community service is effective in improving coordination and technical preparation of the competition, which in turn has a positive impact on the enthusiasm and participation of Pematangsiantar City High School in the quiz competition. In addition, this activity also provides educational experiences for participants regarding the importance of understanding public policy. It is recommended that similar activities be carried out periodically to strengthen community involvement in supporting national policies